2020
DOI: 10.1021/acsmedchemlett.0c00100
|View full text |Cite
|
Sign up to set email alerts
|

From Bacteria to Cancer: A Benzothiazole-Based DNA Gyrase B Inhibitor Redesigned for Hsp90 C-Terminal Inhibition

Abstract: Heat shock protein 90 (Hsp90) is a molecular chaperone that is responsible for the folding and maturation of client proteins that are associated with all ten hallmarks of cancer. Hsp90 N-terminal pan inhibitors have experienced unfavorable results in clinical trials due to induction of the heat shock response (HSR), among other concerns. Novobiocin, a well characterized DNA gyrase B inhibitor, was identified as the first Hsp90 C-terminal inhibitor that manifested anticancer effects without induction of the HSR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 17 publications
1
13
1
Order By: Relevance
“…On the contrary, a known Hsp90 NTD inhibitor 17-DMAG that was used as a positive control resulted in significant upregulation of these heat shock proteins. These data confirmed that this new class of inhibitor modulates the activity of Hsp90 in a CTD allosteric manner, similar to the previously reported benzothiazole-based CTD inhibitors [ 35 ].…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…On the contrary, a known Hsp90 NTD inhibitor 17-DMAG that was used as a positive control resulted in significant upregulation of these heat shock proteins. These data confirmed that this new class of inhibitor modulates the activity of Hsp90 in a CTD allosteric manner, similar to the previously reported benzothiazole-based CTD inhibitors [ 35 ].…”
Section: Resultssupporting
confidence: 90%
“…The benzothiazole moiety was selected as a suitable central scaffold that offers the possibility for the attachment of aromatic substituents and basic amines to positions 2 and 6, which are characteristic for Hsp90 CTD inhibitors ( Figure 1 ). In contrast to the already known benzothiazoles A and B ( Figure 2 ) [ 34 , 35 ], we decided to introduce aromatic groups at position 6 of the benzothiazole moiety and to replace the amide bond at position 2 with an amine directly linked to the benzothiazole ring ( Figure 2 ). This amine would serve as an attachment point for the various linkers to the basic center.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations